The Improvement of Teachers’ Competence in Utilizing The Environment at Public Elementary School 1 of Kalangan Prao as Learning Resource through Teacher Group in The Odd Semester of 2019/2020 Academic Year - Supani . (Pancaran Pendidikan, 2019)
The 2013 curriculum currently in force requires new strategies, especially in learning activities. The learning approach that was previously dominated by the teacher's role (teacher centered) was renewed with a student centered learning system. One of the learning strategies in line with this is learning by utilizing the school environment as a learning resource that allows students to develop creativity, motivation and participation in learning. This research uses action research with two cycles. Each cycle is carried out in four meetings, consisting of four stages, namely: (1) action plan, (2) implementation and (3) observation, and (4) reflection. This School Action Research is located in the Teacher forum at Public Elementary School 1 of Kalangan Prao, Jrengik district, Sampang regency, which is aimed at 6th grade students and 6th grade teachers. The implementation of this research was begun by collecting data using observation sheets, learning plan assessment instrument and learning implementation observation instrument. Furthermore, the data collected has been analyzed using descriptive analysis. From the results of the analysis it was found that the average of the teacher's attitude in the first cycle was 79.38 demonstrating "fair" category, while in the second cycle  it was found at 84.88 demonstrating "good" category. The average value obtained from the assessment of lesson plans in the first cycle was 78,75 indicating "fair", while in second cycle it was found that they achieved 82.50 demonstrating "good" category. The learning assessment in cycle I indicated an average of 78.33 demonstrating "satisfactory" categories, with that in the second cycle being 82.08 which demonstrated "good" category